Back to the drawing board: The economic crisis and its implications for pension provision in the United Kingdom - Frank Eich; Amarendra Swarup (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2009)
This paper focuses on an issue, which so far has received relatively little attention by policy makers and the media, namely that the economic crisis has highlighted inherent weaknesses in existing pension systems in many countries. Using the example of the UK, the paper argues that the economic crisis will usher in further changes to the future provision of pensions, with the role of the private and public sectors likely to evolve in the years ahead. To support this argument, the paper first presents the pension landscape in the UK prior to the crisis, which was dominated by the closure of defined benefit pension schemes in the private sector and the government's reform efforts. The paper then describes the impact of the economic crisis from both a macroeconomic and financial perspective on all aspects of the pension system, from the government's deteriorating public finances to the collapsing funding position of occupational defined-benefit and defined-contribution schemes. The paper concludes by suggesting that the crisis has left the British pension system in a weakened state and that it is unlikely that it will return to its “pre-crisis” status once the economy recovers from the crisis.
Keywords: 330; Economic crisis; Pension finances; Pension systems; Defined benefit pensions; Pension liabilities; Government policy; Financial markets